What is successful integration in primary health care: qualitative insights from the Chinese public - Jinnan Zhang; Rebecca Mitchell; Ruixue Zhao; Mengyao Li; Wenhua Wang (Global Health Action)
Background China is transforming its hospital-centric service delivery system into a people-centered integrated care model, with service delivery organized around the health needs and expectations of people. Objective To guide reforms and align with public expectations, this study profiles successful integration in primary health care from the public perspective. Methods Guided by the rainbow model of integrated care, semi-structured interviews were conducted in six provinces in China. A total of 58 interviewees completed the interviews. Tape-based analysis was used to produce narrative summaries. Researchers listened to the recordings and summarized by 30-s segments. Thematic analysis was performed on summaries to identify thematic families. Results Five themes and 16 sub-themes were generated. Respondents’ expectations were primarily on three themes: clinical integration (such as interaction between professional and client, continuity, and empowering and engaging individuals), functional integration (such as resources management, quality improvement, and reforming payment systems), and system integration (such as institutional distribution and supervision). Yet a few interviewees mentioned professional integration (multi-disciplinary collaboration) and organizational integration (inter-organizational strategy). Conclusions Qualitative data were used to reveal public perceptions of successful primary health care integration. Service processes, institutional distribution, regulation, resource management, and quality improvement are more visible to the public and will be priorities for future efforts. Whereas inter-organizational strategies and multi-disciplinary collaboration have been shown to facilitate service improvements. Future efforts could consider how policy efforts can be grounded in visible service delivery through management practices.